Critical theory and solidarity: normative power of the social action - José Henrique Sousa Assai (Aufklärung, 2016)
Habermas often shows the task of Critical Theory as a critical-reflexive way that is guided by social action in which underlies a particular praxis. But socially act, according to Habermas thought, it is also link subjectivity to a normative understanding and that means, in its vast critical research associate transcendental subject to social being “detranszendentalisierte” aimed at emancipated social order. This argument raises rethink not only the concept of reason, but especially put again the question of reason detranszendentalisierte Vernunft as a ground for solidarity and this because this would be, if the research is plausibel, a possible medium for social praxis whose philosophical ground is given in a conception detranszendentalisierte Vernunft. I intend to explicit the argument that the solidarity can be more than a civic task but also assume a normative task and it reveals its potential normative that is a characteristic of a Critical Theory.